Robot manipulator and controller design - Hashemi, Soheil Bonakdar (Universiti Teknologi PETRONAS, 2007)
Objectives ofthis project are to design and manufacture a robot manipulator arm and the controller. This robot is a high precision robot rather than a heavy duty. As it is supposed to reach points in constant speed and with an approximately zero offset error. The robot to be designed in this project will have three degree of freedom. This robot will be controlled manually and also it will have the ability to be controlled in an automated way by using the aim of computer. In this project microcontrollers will be performing as Communication Bridge between the computer and controller of the robot as well as the controller itself. The robot which is to be manufactured in this project is designed to perform pick and place jobs. The load which is to be treated by this robot is having aweight of1kilogram in the worst case. It meansthe load could either 1 kilogram or less in term of the weight. The problem to be considered in this project is to fined the source point either manually orautomatically exactly as it had been addressed in term ofthe dimensions and then pick the target piece and deliver it to the destination exactly as it had been addressed by the user in a constant speed and acceptable time. Scope ofstudy in this project is to design a feedback control loop which is controlling the robot movement inthe way that it moves smoothly and it reaches every point in the work space exactly as it had been addressed, this aim will be achieved by studying the position of the robot in term of the pulses which will be sent to the microcontroller from the encoders as feedback information, And then affecting the magnitude of the current which is flowing trough the DC motor armature by aid ofH-Bridges and microcontroller. This affect includes maintaining the magnitude of the current, reducing the magnitude of the current, and finally increasing the magnitude ofthe current. The position ofthe robot will be approximated based on the number of pulses which is being detectedby microcontroller.